The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7841/ksbbj.2015.30.5.245
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Enhanced Physiological Activities of Mixed Lactic Acid Bacteria Isolated from Fermented Watery Kimchi, Dongchimi

Abstract: The aim of this study was to investigate the efficacy of enhanced physiological activities in cultures isolated from Korean fermented watery Kimchi, Dongchimi, of single lactic acid bacteria (LAB), and when these three are mixed LAB as probiotics. Using the BIOLOG system and 16S rRNA sequencing, the isolates were characterized, and identified and assigned to Leuconostoc mesenteroides DK-3, Leuconostoc dextranicum DK-6, and Lactobacillus curvatus DK-13, respectively. Growth rate and pH changes, production of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is expected that L. curvatus will be dominant in CD sample during cold storage. It has been reported that L. cruvatus DK-13 isolated from watery Kimchi can produce high amounts of lactic acid and acetic acid during growth on MRS broth [ 28 ]. A starter of sausage, L. curvatus 54M16 can grow at a minimum pH of 3.5 at 30 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that L. curvatus will be dominant in CD sample during cold storage. It has been reported that L. cruvatus DK-13 isolated from watery Kimchi can produce high amounts of lactic acid and acetic acid during growth on MRS broth [ 28 ]. A starter of sausage, L. curvatus 54M16 can grow at a minimum pH of 3.5 at 30 °C.…”
Section: Resultsmentioning
confidence: 99%